Response of soybean rhizosphere communities to human hygiene water addition as determined by community level physiological profiling (CLPP) and terminal restriction fragment length polymorphism (TRFLP) analysis - Kerkhof, Lee; Santoro, Marc; Garland, Jay (FEMS microbiology letters, 2000)
In this report, we describe an experiment conducted at Kennedy Space Center in the biomass production chamber (BPC) using soybean plants for purification and processing of human hygiene water. Specifically, we tested whether it was possible to detect changes in the root-associated bacterial assemblage of the plants and ultimately to identify the specific microorganism(s) which differed when plants were exposed to hygiene water and other hydroponic media. Plants were grown in hydroponics media corresponding to four different treatments: control (Hoagland’s solution), artificial gray water (Hoagland’s+surfactant), filtered gray water collected from human subjects on site, and unfiltered gray water. Differences in rhizosphere microbial populations in all experimental treatments were observed when compared to the control treatment using both community level physiological profiles (BIOLOG) and molecular fingerprinting of 16S rRNA genes by terminal restriction fragment length polymorphism analysis (TRFLP). Furthermore, screening of a clonal library of 16S rRNA genes by TRFLP yielded nearly full length SSU genes associated with the various treatments. Most 16S rRNA genes were affiliated with the Klebsiella, Pseudomonas, Variovorax, Burkholderia, Bordetella and Isosphaera groups. This molecular approach demonstrated the ability to rapidly detect and identify microorganisms unique to experimental treatments and provides a means to fingerprint microbial communities in the biosystems being developed at NASA for optimizing advanced life support operations.